PERMEABILITY CAMPURAN HOT ROLLED SHEET WEARING COURSE (HRS-WC) DENGAN FILLER ABU SEKAM PADI UNTUK JALAN PERKOTAAN - Hery Awan Susanto; Eva Wahyu Indriyanti; Bambang Edison (Universitas Pasir Pengaraian, 2014)
One of the success factors in the construction of the road is a road construction material available qualified technical specifications. Road construction materials in question are aggregated. In addition, the material can be added to the asphalt mixture can form filler that serves as filler. Rice husk ash as waste burning brick able to provide alternative opportunities as an ingredient in asphalt mixtures, as rice husk ash are often found in areas Banyumas.This study aims to determine the permeability properties of a mixture of Hot Rolled Sheet Wearing Course ( HRS - WC ). Permeability is one of the parameters to measure the ability of the asphalt pavement structure that can withstand water seepage damage the asphalt pavement layers. The smaller the value of the permeability of asphalt pavement structure, the more durable the strength of the pavement layers. In the future, besides being able to deliver more value to the utilization of waste rice husk ash, rice husk ash utilization is also expected to increase the permeability of the mixture HRS - WC.